Interactive effects of benthivorous fish disturbance and ammonium loading on two submersed macrophytes of contrasting growth forms based on a mesocosm study - Yu, Qing; Wang, Haijun; Liu, Miao; Xu, Chao; Ma, Yu; Guo, Weihua; Jeppesen, Erik (Frontiers in Environmental Science, 2022)
Benthivorous fish disturbance and nitrogen loading are two important factors that influence the community structure of submersed macrophytes, but their interactive effect is not well elucidated. We conducted an outdoor mesocosm experiment to examine the separate and combined effects of these two factors on the growth of two submersed macrophytes of different growth forms. The treatments involved two levels of fish disturbance crossed with two levels of nitrogen loading. For M. spicatum, we found that fish disturbance alone negatively affected the above-ground biomass (AGB) and its relative growth rate (RGR-AGB), nitrogen alone significantly decreased the maximum height (MH), density, AGB, below-ground biomass (BGB) and RGR-AGB, and their combined effects also negatively impacted these variables. While fish disturbance alone did not affect the growth of V. natans, nitrogen alone drastically reduced its MH, density and AGB, and the combined effect had a negative influence on the density and AGB. Moreover, compared to M. spicatum, the height and RGR-AGB of V. natans were markedly lower in the presence of fish/nitrogen, both alone and when combined. However, both species displayed an increased root biomass to shoot biomass ratio (R/S) in the presence of nitrogen, both with and without fish. Fish activity significantly increased the concentration of total suspended solids (TSS) in the water, while total nitrogen (TN), ammonium, total phosphorus (TP), light, pH and salinity were not affected. When fish and nitrogen were combined, TN, TP, TSS and salinity increased significantly, while pH decreased. Meanwhile, no differences among treatments were observed for chlorophyll a concentration in the V. natans enclosures, while the chlorophyll a concentration in the M. spicatum enclosures was significantly higher in both the nitrogen treatment and the fish and nitrogen treatment compared to control treatment. Our study suggests that (1) fish disturbance and nitrogen loading may have a synergistic negative effect on the population growth of M. spicatum, and the stress effect of high-N makes M. spicatum more sensitive to low light stress caused by fish disturbance, and (2) an increased R/S might dampen the negative effects of high N, buffering the impact of N loading on aquatic ecosystems.